Failure mechanisms of corroded/non-corroded RC cylinder under axial compressive loading evaluated by AE technique - Seye, Mouhamadou Mountakhah; Kawasaki, Yuma (Frontiers in Built Environment, 2022)
This study applied acoustic emission (AE) technique to investigate mechanical behaviors and failure processes of corroded and non-corroded reinforced concrete (RC) cylinders, subjected to compressive loading. RC cylinders with 150 mm diameter and 300 mm height were tested. One set of twelve specimens was arranged into four groups of three specimens. These were the specimens corroded at the initiation stage, at the acceleration stage, at the deterioration stage of rebars, and another group was prepared as non-corroded specimens. The other set of twelve specimen were corroded as the same as the one, but axial rebars were coated with epoxy-resin. After performing electrical corrosion, by applying 200 mA current under salt-water immersion of 3% chloride concentration, axial compression tests were conducted on all specimens up to failure, using AE technique. The corrosion of rebars inside the cylinders trend to decrease the compressive load-carrying performance of the RC cylinders, with the occurrence of early damages during the axial compression test. The analysis of the measured AE parameters enabled the classification of the generated damages into shear-type and tensile-type damages, which provided a characteristic signature of the failure mechanism of the tested cylinders. Next, it provided a 3D visualization of the damage events location, and evolution inside the cylinders. Then, it gave the means to correlate the damage process of the RC cylinders, with their specific condition related to their corrosion level, prior to the compression test.